Lactational High Fat Diet in Mice Causes Insulin Resistance and NAFLD in Male Offspring Which Is Partially Rescued by Maternal Metformin Treatment - Hafner, Hannah; Mulcahy, Molly C.; Carlson, Zach; Hartley, Phillip; Sun, Haijing; Westerhoff, Maria; Qi, Nathan; Bridges, Dave; Gregg, Brigid (Frontiers in Nutrition, 2021)
Maternal metabolic disease and diet during pregnancy and lactation have important implications for the programming of offspring metabolic disease. In addition, high-fat diets during pregnancy and lactation can predispose the offspring to non-alcoholic fatty liver disease (NAFLD), a rising health threat in the U.S. We developed a model of maternal high-fat feeding exclusively during the lactation period. We previously showed that offspring from dams, given lactational high-fat diet (HFD), are predisposed to obesity, glucose intolerance, and inflammation. In separate experiments, we also showed that lactational metformin treatment can decrease offspring metabolic risk. The purpose of these studies was to understand the programming implications of lactational HFD on offspring metabolic liver disease risk. Dams were fed a 60% lard-based HFD from the day of delivery through the 21-day lactation period. A subset of dams was also given metformin as a co-treatment. Starting at weaning, the offspring were fed normal fat diet until 3 months of age; at which point, a subset was challenged with an additional HFD stressor. Lactational HFD led male offspring to develop hepatic insulin resistance. The post-weaning HFD challenge led male offspring to progress to NAFLD with more severe outcomes in the lactational HFD-challenged offspring. Co-administration of metformin to lactating dams on HFD partially rescued the offspring liver metabolic defects in males. Lactational HFD or post-weaning HFD had no impact on female offspring who maintained a normal insulin sensitivity and liver phenotype. These findings indicate that HFD, during the lactation period, programs the adult offspring to NAFLD risk in a sexually dimorphic manner. In addition, early life intervention with metformin via maternal exposure may prevent some of the liver programming caused by maternal HFD.